The eBario Story : ICTs for Rural Development - Roger, Harris; Narayanan, A/L N. Kulathu Ramaiyer; Tarawe, John (2018)
Malaysia’s eBario project has had a seminal influence on policy and professional practice in ICT4D for rural development, especially for remote and isolated communities of indigenous minorities. Direct impacts have delivered benefits for improved skills, incomes, health, education, cultural preservation, agriculture and social communications for participating communities. Wider impacts include influence on national policy-making and the operation of development interventions as well as providing important insights into the conduct of ICT4D research that seeks to improve the lives of marginalised and underserved communities.